The Danish Welfare State A Sociological Investigation - Frederiksen, Morten. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
The Danish Welfare State analyzes a broad range of areas, such as globalization, labor marked, family life, health and social exclusion, the book demonstrates that life in a modern welfare state is changing rapidly, creating both challenges and possibilities for future management.